Development Of An Integrated Science E-Module Oriented Problem Based Learning On Organ Systems Material For Class VIII SMP - Wahyuni, Setio Putri Ayu Sri; Yurnetti, Yurnetti; Lestari, Tuti; Putri, Azza Nuzullah (Department of Science Education, 2024)
The Kurikulum Merdeka provides freedom for schools, educators and students to innovate, learn creatively and independently. Then, along with the technology development, teachers are also demanded to innovate materials for teaching to help the process of learning in related with the curriculum. The results of observations in the field shown that the material for teaching used have few practice questions related to daily life and the material is quite dense, so teaching materials are needed that contain more questions related to daily life. To overcome this problem, the innovation provided is an Integrated Science E-module Oriented to Problem Based Learning. The research aims are to produce an Integrated Science E-Module Oriented to Problem Based Learning on Organ System Material that is has validity and practicality to use for class VIII SMP students. The research type used is research and development (R&D), using a 4-D model which have 4 phases, that are define, design, develop and disseminate. However, the research just conducted until the development phase. The instruments in this research were a validation questionnaire sheet and a practicality questionnaire sheet. The test of validity results obtained a value of 83.43% in the category in very valid. The test of practicality results by the teacher obtained a score of 98.61% in the category in very practical and the test of practicality results by students obtained a score of 89.51% in the category in very practical. According on these results, the conclusion that the Integrated Science E-Module with Problem Based Learning Orientation on Organ System Material has met the valid and practical category for use by class VIII SMP students.